2022
DOI: 10.1192/bjp.2022.103
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre, England-wide randomised controlled trial of the ‘Foundations’ smartphone application in improving mental health and well-being in a healthcare worker population

Abstract: Background Healthcare workers (HCWs) have faced considerable pressures during the COVID-19 pandemic. For some, this has resulted in mental health distress and disorder. Although interventions have sought to support HCWs, few have been evaluated. Aims We aimed to determine the effectiveness of the ‘Foundations’ application (app) on general (non-psychotic) psychiatric morbidity. Method We conducted a multicentre randomised controlled trial of HCWs at 16 NHS trusts (trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 40 publications
(67 reference statements)
1
42
1
Order By: Relevance
“…During the COVID-19 pandemic, some RCTs used online and phone-based emotion regulation interventions similar to the first step of our programme, namely DWM. Their effects on anxiety and depression symptoms were either non-existent8 11 13 or limited to the completion of a unique mindfulness training session 6 7. This contrasts with our positive findings with the DWM at 6 weeks from baseline, probably because it was more intense both in terms of duration (5 weeks vs 2–4 weeks) and level of support (weekly follow-up calls vs unguided self-help) 35 36.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…During the COVID-19 pandemic, some RCTs used online and phone-based emotion regulation interventions similar to the first step of our programme, namely DWM. Their effects on anxiety and depression symptoms were either non-existent8 11 13 or limited to the completion of a unique mindfulness training session 6 7. This contrasts with our positive findings with the DWM at 6 weeks from baseline, probably because it was more intense both in terms of duration (5 weeks vs 2–4 weeks) and level of support (weekly follow-up calls vs unguided self-help) 35 36.…”
Section: Discussioncontrasting
confidence: 77%
“…However, most have used short psychological interventions with no previous evidence, included small sample sizes (mostly limited to nurses) and used short follow-up periods. Two studies reported positive results on anxiety symptoms, but only immediately after a single mindfulness training session,6 7 and one reported a decrease in general psychiatric comorbidity at 8 weeks from baseline using a smartphone app but did not find any effects on anxiety or depression symptoms 13…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Five studies used web applications to deliver psychological interventions (Fiol‐DeRoque et al., 2021; Ghazanfarpour et al., 2021; Gnanapragasam et al., 2022; Gupta et al., 2021; Otared et al., 2021). Two studies did not show significant differences between groups for the primary outcomes (Fiol‐DeRoque et al., 2021; Gupta et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Gnanapragasam et al. (2022) used the Foundations smartphone application, the main aim of this tool was to promote well‐being habits and behaviour change, promoting mental well‐being, improving sleep and managing stress. Participants in the application group presented a significant reduction of psychiatric morbidity symptoms (aMD = −1.39, 95% CI = −2.05 to −0.74, p < 0.001) as well as a significant increase in well‐being (aMD = 0.54, 95% CI = 0.20–0.89, p = 0.002) compared to control group.…”
Section: Resultsmentioning
confidence: 99%